Bartonella spp. as a Possible Cause or Cofactor of Feline Endomyocarditis–Left Ventricular Endocardial Fibrosis Complex. (July 2018) - Donovan, T.A.; Balakrishnan, N.; Carvalho Barbosa, I.; McCoy, T.; Breitschwerdt, E.B.; Fox, P.R.
Summary: Endomyocarditis is a commonly detected post-mortem finding in domestic cats presenting for sudden onset cardiovascular death, yet the aetiology remains unresolved. Cats are documented reservoir hosts for Bartonella henselae, the infectious cause of cat scratch disease in man. Various Bartonella spp. have been associated with culture-negative endocarditis, myocarditis and sudden death in man and animals. We hypothesized that Bartonella spp. DNA could be amplified more often from the hearts of cats with feline endomyocarditis–left ventricular endocardial fibrosis (FEMC–LVEF) complex compared with cats with hypertrophic cardiomyopathy (HCM) or cats with grossly and microscopically unremarkable hearts (designated non-cardiac disease controls). Formalin-fixed and paraffin wax-embedded, cardiac tissues from 60 domestic and purebred cats aged 3 months to 18 years were examined, and histological features were recorded. Cardiac tissue sections were tested for Bartonella DNA using multiple 16–23S intergenic transcribed spacer region polymerase chain reaction (PCR) primer sets, including two Bartonella genera, a Bartonella koehlerae species-specific and a Bartonella vinsonii subsp. berkhoffii -specific assay, followed by DNA sequence confirmation of the species or genotype. Special precautions were taken to avoid DNA cross-contamination between tissues. Bartonella spp. DNA was amplified by PCR and sequenced from 18 of 36 cats (50%) with FEMC–LVEF and 1/12 (8.3%) cats with HCM. Bartonella spp. DNA was not amplified from any non-cardiac disease control hearts. Based on PCR/DNA sequencing, one Bartonella spp. was amplified from 10 cats, while the remaining eight were coinfected with more than one Bartonella spp. To our knowledge, this study represents the first documentation of B . vinsonii subsp . berkhoffii genotype I infection in cats ( n = 11). Fluorescence in-situ hybridization testing facilitated visualization of Bartonella bacteria within the myocardium of four of seven PCR-positive FEMC–LVEF hearts. Collectively, these findings support the hypothesis that Bartonella spp. may play a primary role or act as a cofactor in the pathogenesis of FEMC–LVEF. Studies involving cats from other geographical regions and definitive demonstration of Bartonella spp. within regions of inflammation are needed to confirm an association between Bartonella spp. and FEMC–LVEF induced morbidity and mortality in cats. Graphical abstract: